Gastric-targeted drug delivery by learning from Helicobacter pylori - Paraskevopoulou, Vasiliki (2019)
Drugs which would preferentially be absorbed through the stomach or upper small intestine are characterised by a narrow absorption window, due to their rapid transit time through these regions of the gastrointestinal tract and the insufficient contact time with their site of absorption. In order to address the problem of low bioavailability, which is related to the narrow absorption window, the development of drug delivery systems which adhere to the gastric epithelium and retain the drug in the stomach was an appealing approach. The present study suggests the exploitation of adhesins from Helicobacter pylori, in order to generate gastric-targeted drug delivery carriers, which mimic the bacterial mechanism and adhere to the gastric epithelium. In the present work, four different H. pylori adhesins were recombinantly expressed at a range of yields in the periplasmic space of Escherichia coli; the highest yield was observed for LabA. Although it did not influence the expression yield, the presence of a C terminal hexalysine tag in the expression construct of LabA enhanced the protein’s thermal stability and aqueous solubility, without affecting its secondary structure. The enhancement of solubility imposed obstacles to protein crystallisation; redesign of the expression construct led to the acquisition of protein crystals and a crystal structure, which was the biggest achievement of this work, as the crystal structure of LabA J99 has not been published. Although the crystal structure was determined, no specific ligands were identified for LabA J99. Consequently, recombinant BabA with known affinity for Leb was used to decorate model gastric targeted microparticles. After confirming the binding affinity of the BabA conjugated microparticles for Leb, polymer coating of the surface of the microparticles was examined for its protective effect against pepsin digestion of BabA, which constitutes the main challenge for the viability of the microparticles in vivo.